Adult WHO grade II ependymomas: is Ki67 a sex-specific proliferation marker?. Issue 8 (24th August 2021) - Baig Mirza, Asfand; Lavrador, José Pedro; Mancuso-Marcello, Marco; Acharya, Shami; Boardman, Timothy Martyn; Bodi, Istvan; Gullan, Richard; Vergani, Francesco; Bhangoo, Ranj; Ashkan, Keyoumars
Abstract: Ki67 is a marker for proliferation of a given cell population. Low expression of Ki67 may be associated with a favourable outcome. We investigate how the proliferation index correlates with the location, morphology and behaviour of WHO grade II ependymomas with a single-centre cohort study of adult patients admitted for surgery of WHO grade II ependymomas between 2008 and 2018. Seventeen patients were included, seven had supratentorial and 10 had infratentorial tumours. Three patients died and eight had recurrent disease. Age, gender, location, extent of resection, chemotherapy, radiotherapy and histological markers were not associated with tumour progression. Both unadjusted and adjusted analysis confirmed a higher Ki67 index in male patients. Sensitivity analysis further supported the correlation between Ki67 and male gender. Ki67 may be sex specific but does not seem to correlate with survival and time to recurrence in this series.